The Effectiveness of Malay Ethnomathematics-Based PMRI on the Numeracy Literacy of Junior High School Students - Syahriani Sirait (Universitas Negeri Semarang, 2026)
This study analysed the effectiveness of Malay ethnomathematics-based mathematics learning using the Indonesian Realistic Mathematics Education (PMRI) approach on the numeracy literacy of seventh-grade students at SMP Negeri 7 Kisaran. A quasi-experimental method with a nonequivalent control group design was employed. The participants were 64 students, consisting of an experimental class (n = 32) and a control class (n = 32). The experimental class learned through PMRI activities using Malay-Asahan cultural contexts, including traditional market transactions, songket motifs, local measurements, and daily community practices, whereas the control class received conventional instruction. Data were collected using essay-based numeracy literacy tests validated by experts and tried out before implementation. The results showed that the two classes had comparable initial ability (pretest means of 52.3 and 51.8; Sig. = .803). After the treatment, the experimental class achieved a higher posttest mean score (81.4) than the control class (70.2). The independent samples t-test indicated a significant difference (t = 5.42; df = 62; Sig. < .001) with a large effect size (Cohen’s d = 1.36). The experimental class N-gain (0.61) was also higher than the control class N-gain (0.38). These findings indicate that Malay ethnomathematics-based PMRI effectively improves students’ numeracy literacy.